Pengaruh Transformasi Digital terhadap Sustainability Accounting and Reporting Indonesia: Green Economy Catalyst - Inna Zahara; Ari Okta Viyani; Sumayyah Sumayyah (Universitas Muhammadiyah Metro, 2026)
Driven by the global shift towards a green economy, this study empirically investigates the impact of digital transformation on Sustainability Accounting and Reporting (SAR) practices among listed companies on the Indonesia Stock Exchange. This research analyzes secondary data from 36 companies that adopted ESG principles in 2023. The quantitative data collected was processed and analyzed using simple linear regression and Moderated Regression Analysis (MRA). The research findings indicate that the influence of digital transformation on SAR is minimal, as evidenced by the regression coefficient approaching zero. This suggests a weak and potentially negative relationship between digital transformation and SAR practices. However, moderation regression analysis revealed that firm size significantly strengthens the relationship between digital transformation and SAR practices. These findings imply that while digital transformation offers the potential to enhance SAR practices, companies require sufficient resources, similar to those possessed by larger corporations, to effectively leverage this potential.